Synthesis, spectroscopy and redox properties of a novel (E-E) vic-dioxime and its mono-, di- and trinuclear complexes bearing an 18-membered N2O2S2 macrocyle - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
A new 18-membered figand, 2,3-dibromo-6,7,13,14,15,16,22,23-octahydro 14, 15-bis(hydroxyimino)-tribenzo [e,k,q] [1,4,10,13,7,16] diazadioxadithiacyclooctadecine (LH4) containing three different heteroatoms (N-, O-, S-) has been prepared from 1,2-bis (2'-amino phenylsulfanylethoxy)-4,5-dibromobenzene and cyanogen di-N-oxide. Mononuclear (LH3)(2)M, where M = Ni(II), Cu(II), Co(II), Fe(II) binuclear (LH)(2)(UO2)(2)(OH)(2) and trinuclear (LH)(2)M-3, where M = Cu (II), Co (II) complexes of LH4 have been obtained with a metal:ligand ratio 1:2, 2:2 and 3:2, respectively, through N,N-coordinating or N, N, S, S-coordinating in the presence of a base, as do most of the vic-dioximes. H-1 NMR, IR, UV-Vis and MS data are presented. The cyclic voltammetric (CV) measurements of the newly synthesized compounds were measured. Voltammetric results showed that oxime-containing ligands stabilize Ni(III), Fe(III), Co(III) and Cu(III). The Fe(II) complex displayed a different behavior with respect to other complexes. This indicated that both Fe(III) and Fe(I) species are stable while oxime containing ligands tend to stabilize only one of the oxidized forms of the metal center of the complexes. Differently, ligand based reduction was recorded only with the Ni(II) complex. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: vic-dioxime; nickel(II); cobalt(II); copper(H); iron(H); uranyl(M; electrochemistry; LH4; N2O2S2 macrocyle; TRANSITION-METAL-COMPLEXES; ELECTROCHEMICAL PROPERTIES; MOLECULAR-STRUCTURE; PHTHALOCYANINES; COPPER(II); NICKEL(II); MONOAZACROWN; TECHNETIUM; CHEMISTRY; CRYSTAL